2011
DOI: 10.1002/chem.201102074
|View full text |Cite
|
Sign up to set email alerts
|

Heteroscorpionate Rare‐Earth Metal Zwitterionic Complexes: Syntheses, Characterization, and Heteroselective Catalysis on the Ring‐Opening Polymerization of rac‐Lactide

Abstract: Novel neutral phosphine-modified heteroscorpionate ligand (3,5-Me(2)Pz)(2)CHPPh(2) (1) and its derivatives oxophosphine (2) and iminophosphine (3) heteroscorpionates were synthesized for the first time. These neutral heteroscorpionate ligands displayed unique chemistry towards rare-earth metal tris(alkyl)s [Ln(CH(2)SiMe(3))(3)(thf)(2)] (Ln=Y, Lu, Sc). The reaction between compound 1 and [Ln(CH(2)SiMe(3))(3)(thf)(2)] afforded heteroscorpionate rare-earth metal trialkyl adduct complexes 4a-c. Compounds 2 and 3 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
33
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 76 publications
4
33
0
Order By: Relevance
“…The two lutetium complexes 1 and 2 are approximately an order of magnitude slower than yttrium complexes A and B ( k obs =6.9×10 −4 , 7.9×10 −4 s −1 ). This finding is consistent with other examples of lutetium complexes 10b,f,h,j. 13 In contrast, lanthanum complex 3 was an extremely fast initiator, enabling almost complete conversion of 1000 equivalents of LA [versus initiator, in the presence of isopropyl alcohol (2 equivalents)] in less than 20 seconds (Table 1).…”
Section: Methodssupporting
confidence: 89%
See 1 more Smart Citation
“…The two lutetium complexes 1 and 2 are approximately an order of magnitude slower than yttrium complexes A and B ( k obs =6.9×10 −4 , 7.9×10 −4 s −1 ). This finding is consistent with other examples of lutetium complexes 10b,f,h,j. 13 In contrast, lanthanum complex 3 was an extremely fast initiator, enabling almost complete conversion of 1000 equivalents of LA [versus initiator, in the presence of isopropyl alcohol (2 equivalents)] in less than 20 seconds (Table 1).…”
Section: Methodssupporting
confidence: 89%
“…The use of different lanthanide centers enables an investigation of the influence of atomic size and coordination environment on polymer tacticity. Both metals have precedence in lactide ROP catalysis,10 although lutetium is rarely investigated 10b,e,f,h. Okuda and co‐workers reported heteroselective (syndiotactic) dithiaalkanediyl‐bridged bis(phenolato) yttrium and lutetium catalysts, but found that the stereocontrol decreased from Y to Lu 10b,f.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the molecular weight of the polymers increases linearly with the ratio of [ rac ‐LA] 0 /[ 1a ] 0 (Table , entries 2, 9–12), which strongly suggests the controllable polymerization processes were initiated by complex 1a (SI Figure S20). These experimental results reveal that monoguanidinate rare‐earth metal aminobenzyl enolate complexes display efficient catalytic activity in the ROP of rac ‐lactide …”
Section: Resultsmentioning
confidence: 79%
“…It is noteworthy that this compound has been demonstrated to be a potent inhibitor of the Kv1.5 potassium channel and a possible treatment for atrial fibrillation. 8a The prior synthesis provided only 2% yield of this biologically interesting compound, whereas the yield was significantly improved employing our method.…”
mentioning
confidence: 92%
“…8 Surprisingly, very few methods have been reported for their synthesis. Classical methods involve the use of Michaelis-Arbuzov or Michaelis-Becker reactions (Scheme 1).…”
mentioning
confidence: 99%